Trends in Medical Claims and Utilization of Limited Ultrasonography Among Emergency Physicians and Radiologists Within a Large Health Plan Provider. (12th September 2018) - Bergmann, Kelly R.; Reardon, Robert F.; Flores, Glenn; Whitcomb, Valerie; Christensen, Eric W.; Watson, Dave; Kharbanda, Anupam
Abstract : Objectives: The goal of this study was to evaluate trends in medical claim submissions for limited ultrasound studies performed (1) during emergency department (ED) encounters and (2) by ED providers compared to radiologists. Methods: We conducted a retrospective, descriptive study using medical claims data from Medica Health Plans from January 1, 2011 to December 31, 2015. Current procedural terminology codes were abstracted for limited ultrasound applications performed during an ED visit and further stratified by studies performed by ED providers compared with radiologists. We excluded claims for which we could not determine provider specialty. Results: We identified 42, 576 encounters with limited US claims, of which, 32, 666 were submitted by ED providers (N = 9649) or radiologists (N = 23, 017). Among ED providers, there was a significant linear increase in the annual number of claims for retroperitoneal ( P  < .001) and nonlinear increases for thoracic, soft tissue, cardiac, transvaginal genitourinary (GU) and transabdominal GU claims (all P  < .001). Compared with radiologists, there was a linear increase in the annual proportion of claims submitted for retroperitoneal ( P  = .023), transabdominal GU ( P  = .003), and transvaginal GU ( P  < .001) studies by ED providers. There was a nonlinear decrease in the annual proportion of limited abdomen claims ( P  < .001) submitted by ED providers compared with radiologists. Conclusions: Using data from a large health plan provider, we show that medical claims for many limited ultrasound studies are increasing among ED providers. Compared with radiologists, ED providers are increasingly submitting claims for retroperitoneal, soft tissue, and transabdominal GU studies.